Space-time clustering and temporal trend analysis of pulmonary tuberculosis in Brazil, 2010–2023 - José Mário Nunes da Silva; Fredi Alexander Diaz-Quijano; Lívia Teixeira de Souza Maia; Mauro Niskier Sanchez; Ximena Pamela Claudia Díaz Bermúdez; Eduardo de Souza Alves; Walter Massa Ramalho (PLoS ONE, 2026)
Background Identifying high-risk areas for pulmonary tuberculosis (PTB) is essential for understanding the dynamics of disease transmission and for guiding more effective control strategies. Therefore, this study aimed to analyze the temporal trends and spatiotemporal distribution of PTB across Brazilian municipalities between 2010 and 2023. Methods This is an ecological study using data on PTB cases reported in Brazil’s Notifiable Diseases Information System (SINAN) from 2010 to 2023. Time series analysis, global and local spatial autocorrelation, and space-time scan techniques were applied to identify temporal trends and spatial patterns of the disease at the municipal level. Results A total of 896,062 new PTB cases were analyzed. Notification peaked mainly in March and August. The average incidence rate was 30.3 cases per 100,000 inhabitants-years. An increasing trend was observed in 13 states and the Federal District. Spatial analysis identified 804 municipalities as hotspots, with 168 showing persistent high incidence throughout the study period. A total of 28 spatiotemporal clusters were detected, involving 379 municipalities, of which 212 were classified as high priority. The most likely cluster was located in the Rio de Janeiro Metropolitan Region, encompassing 10 municipalities, with a relative risk (RR) of 2.51 between 2017 and 2023. Spatial variation in temporal trends identified 22 additional clusters, including a prominent cluster composed of 493 municipalities in the Legal Amazon, which showed an internal time trend of 1.99% annual growth and a RR of 1.51. Conclusion The study identified persistent and expanding patterns of PTB in Brazil at both regional and national levels, revealing specific areas with higher burden and increasing trends that should be prioritized. These findings provide evidence to support decision-making at federal level while reinforce the need for regionally tailored surveillance and control strategies to ensure a more effective and equitable response to tuberculosis across the country.